Mengangkat Citra Meluaskan Agama: Kiprah Humas Pondok Pesantren Tanpa Kyai di Kabupaten Tebo Provinsi Jambi - Arfan, Arfan; Zakiah, Zakiah; Afriansyah, Afriansyah (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2023)
ABSTRACT: The Bustanil Inshaf Islamic Boarding School, Tebo Regency, Jambi Province, was established in 2020. The founder of this Islamic Boarding School is not Kyai an Educator, but an entrepreneur who intends to invite the local community to take their children to study Islam. A year later the manager of the Islamic boarding school established a Public Relations (PR) section aimed at socializing the existence of this institution and attracting the interest of the surrounding community to take their children to study at the boarding school. This article will describe the communication strategy of the PR organization and the obstacles experienced in improving the image of the Bustanil Inshaf Islamic Boarding School. Using qualitative data, through interviews with 10 informants in March 2022, as well as observations of Islamic Boarding School Public Relations activities, the study found that the PR communication strategy for improving the image of the Bustanil Inshaf Islamic Boarding School is to build direct, active and good communication with multiple parties, namely: the community, local leaders and government agencies. Public Relations is also active in communicating through social media. The parents of the students were also asked to help spread the news about the existence of this Islamic Boarding School. The news about the extracurricular activities of active students and the strategic location of the Islamic Boarding School has made the image of the Islamic Boarding School increase. Barriers experienced by the PR are minimal resources with knowledge of multi-media publications that have not been optimal. However, these obstacles did not prevent the Public Relations of the Bustanil Inshaf Islamic Boarding School from trying to raise its image to spread religious teachings to the younger generation.